Macro and Micro Element Contents in Fruitin Bodies of Wild Edible Mushrooms from Mugla in Southwest Anatolia, Turkey - Erdogan, Sait; Yilmaz-Ersela, Fadime; Merdivan, Melek (Asian Journal of Chemistry, 2010)
The macro (K, Na, Mg, Ca) and micro (Fe, Zn, Co, Mn, Cd, Co, Ni) element contents in 8 different wild edible mushroom species were studied in Southwest Anatolia, Turkey. The study investigated the differences in metal accumulation in relation to species. The mean concentrations of metals in the individual species did not vary to a large extent. The tricholomataceae species in this study had higher protein values than the others. The highest mean concentration of macro elements was found for K (135 g/kg), followed by Mg (1.23 g/kg), Na (0.58 g/kg) and Ca (0.33 g/kg) in Tricholoma terreum (Schff.: Fr.) Kummer. The mean concentrations of microelements for all species were in the following order: Fe > Zn > Cu > Mn > Ni > Cd. Pb and Co were not detected in the studied species. The highest amount of microelements was determined for Cd (8.83 mg/kg), Fe (268 mg/kg) and Zn (100 mg/kg) in T. terreum and for Cu (53.1 mg/kg) and Mn (23.5 mg/kg) in Clitocybe alexandri (Gill.) Konr.